2021
DOI: 10.1021/acs.energyfuels.0c04231
|View full text |Cite
|
Sign up to set email alerts
|

Cerium Oxide-Based Catalysts for Low-Temperature Selective Catalytic Reduction of NOx with NH3: A Review

Abstract: The selective catalytic reduction (SCR) of NO x with ammonia is an effective method to remove NO x from stationary and mobile sources. Cerium oxides (CeO x ) have been studied extensively as low-temperature SCR catalysts since they manifest prominent oxygen storage capacity in catalysis. This paper reviews the recent progress on the Ce-based catalysts for low-temperature SCR de-NO x with NH 3 , including three categories, single CeO x , Ce-based multimetal oxide, and Ce-based multimetal oxides with support. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(35 citation statements)
references
References 176 publications
0
35
0
Order By: Relevance
“…The other reason was that SO 2 could easily react with the active components of MnO xbased catalysts in the presence of O 2 , which sulfated the active center atoms and generated metal sulfates on the surface, leading to the loss of active components, interrupting the redox cycle between metals of different valence states of the catalyst and causing permanent deactivation of the catalyst. 117,118 For the pure MnO x catalyst, the ''synergistic poisoning'' of H 2 O and SO 2 accelerated the formation of metal sulfate and ammonium sulfate on the surface, which expedited the deactivation of the catalyst. 119 Choosing other metals as sacrificial sites to safeguard active MnO x species was also an effective way to enhance the resistance of catalysts to SO 2 .…”
Section: Poisoning Mechanism and Poison-resistant Measures Of Somentioning
confidence: 99%
“…The other reason was that SO 2 could easily react with the active components of MnO xbased catalysts in the presence of O 2 , which sulfated the active center atoms and generated metal sulfates on the surface, leading to the loss of active components, interrupting the redox cycle between metals of different valence states of the catalyst and causing permanent deactivation of the catalyst. 117,118 For the pure MnO x catalyst, the ''synergistic poisoning'' of H 2 O and SO 2 accelerated the formation of metal sulfate and ammonium sulfate on the surface, which expedited the deactivation of the catalyst. 119 Choosing other metals as sacrificial sites to safeguard active MnO x species was also an effective way to enhance the resistance of catalysts to SO 2 .…”
Section: Poisoning Mechanism and Poison-resistant Measures Of Somentioning
confidence: 99%
“…Ce has become the preferred cation for modification as a result of its unique oxygen storage and release properties. 23 After the addition of Ce additives, the catalyst Ce−Cu−ZSM-5 can reach 70% conversion of NO at 350 °C without any obvious "oxygen inhibition" phenomenon. 168 170 prepared Ce-, Sn-, and Ti-doped Cu− ZSM-5 by a co-exchange method and found that the additive doped affects the distribution of Cu in the zeolite, reduces Cu in the aggregated state, and increases more active centers.…”
Section: Cu−zsm-5-catalyzed Decomposition Of Nomentioning
confidence: 99%
“…Shi et al found that Ni-doped Ni–Cu–ZSM-5 had higher NO decomposition activity than Cu–ZSM-5 and significantly improved the O 2 resistance of the catalyst. Ce has become the preferred cation for modification as a result of its unique oxygen storage and release properties . After the addition of Ce additives, the catalyst Ce–Cu–ZSM-5 can reach 70% conversion of NO at 350 °C without any obvious “oxygen inhibition” phenomenon .…”
Section: Cu–zsm-5-catalyzed Decomposition Of Nomentioning
confidence: 99%
See 1 more Smart Citation
“…To be an interesting candidate for automotive Diesel applications, such catalyst must support the severe conditions of vehicle engine and show a high hydrothermal stability up to 800 °C [10][11][12][13][14]. Recently, Ce-based catalysts [15][16][17][18] have also received considerable attention for NO removal through the NH 3 -SCR process thanks to its single properties to combine elevated oxygen transport capacity and to shift easily between Ce 4+ /Ce 3+ reduced and oxidized states [19][20][21]. Since cerium species are known to favour the oxidation of NO to NO 2 , considered as the key step of the standard NH 3 -SCR reaction in the presence of O 2 , Ce-promoted zeolites seems to be promising catalysts for NO abatement through the SCR process [11].…”
Section: Introductionmentioning
confidence: 99%